Eating Behaviour in the General Population: An Analysis of the Factor Structure of the German Version of the Three-Factor-Eating-Questionnaire (TFEQ) and Its Association with the Body Mass Index. - Loffler, A.; Luck, T.; Then, F. S.; Sikorski, C.; Kovacs, P.; Bottcher, Y.; Breitfeld, J.; Tonjes, A.; Horstmann, A.; Loffler, M.; Engel, C.; Thiery, J.; et al. (PLoS One, 2015)
The Three-Factor-Eating-Questionnaire (TFEQ) is an established instrument to assess eating behaviour. Analysis of the TFEQ-factor structure was based on selected, convenient and clinical samples so far. Aims of this study were (I) to analyse the factor structure of the German version of the TFEQ and (II)--based on the refined factor structure--to examine the association between eating behaviour and the body mass index (BMI) in a general population sample of 3,144 middle-aged and older participants (40-79 years) of the ongoing population based cohort study of the Leipzig Research Center for Civilization Diseases (LIFE Health Study). The factor structure was examined in a split-half analysis with both explorative and confirmatory factor analysis. Associations between TFEQ-scores and BMI values were tested with multiple regression analyses controlled for age, gender, and education. We found a three factor solution for the TFEQ with an 'uncontrolled eating', a 'cognitive restraint' and an 'emotional eating' domain including 29 of the original 51 TFEQ-items. Scores of the 'uncontrolled eating domain' showed the strongest correlation with BMI values (partial r = 0.26). Subjects with scores above the median in both 'uncontrolled eating' and 'emotional eating' showed the highest BMI values (mean = 29.41 kg/m(2)), subjects with scores below the median in all three domains showed the lowest BMI values (mean = 25.68 kg/m(2); F = 72.074, p<0.001). Our findings suggest that the TFEQ is suitable to identify subjects with specific patterns of eating behaviour that are associated with higher BMI values. Such information may help health care professionals to develop and implement more tailored interventions for overweight and obese individuals.
Keywords: Adult; Aged; Body Mass Index; Cohort Studies; Eating/*physiology/*psychology; Emotions/physiology; Factor Analysis, Statistical; Feeding Behavior/*physiology/*psychology; Female; Germany; Humans; Male; Middle Aged; Obesity/physiopathology/psychology; Surveys and Questionnaires